Next-generation sequencing of BRCA1 and BRCA2 in breast cancer patients and control subjects - BALABANSKI, LUBOMIR; ANTOV, GEORGI; DIMOVA, IVANKA; IVANOV, SAMUIL; NACHEVA, MARIA; GAVRILOV, IVAN; NESHEVA, DESISLAVA; RUKOVA, BLAGA; HADJIDEKOVA, SAVINA; MALINOV, MAXIM; TONCHEVA, DRAGA (Molecular and clinical oncology, 2014)
Breast cancer is currently the most common type of cancer in females. The majority of the hereditary forms of breast cancer are caused by mutations in the BRCA1 and BRCA2 genes, whose main function is the DNA repair of double-strand breaks. Genetic testing of females with a family history of breast cancer is recommended to determine their hereditary predisposition for this type of cancer. The variants with no clear clinical significance may represent a diagnostic challenge when performing targeted resequencing. In this study, DNA samples were obtained from 24 breast cancer patients (mean age, 35±10 years) with a positive family history and from 71 age-matched healthy controls. Informed consent was obtained from all the subjects. Sequence-targeted BRCA1 and BRCA2 libraries were prepared using the TruSeq Custom Amplicon method and sequenced on the Illumina MiSeq system. A wide range of variants were identified in the BRCA1 and BRCA2 genes. Two pathological/presumably pathological variants were detected in the breast cancer patient group: a mutation in BRCA2 at the chromosomal (chr) position chr13:32890665, which affected the first position of the 5' splice region following exon 2; and a mutation in BRCA1 at chr17:41219635, causing an in-frame triple nucleotide deletion of valine 1688 (8.3%). In the patient and control groups, 7 likely polymorphic variants and 13 common variants were detected in the BRCA1 and BRCA2 genes. To the best of our knowledge, this study was the first to identify 3 common polymorphisms in BRCA2, characteristic solely of the Bulgarian population, including chr13:32973737, T/-, a single-nucleotide polymorphism (SNP) within the 3'-UTR of exon 27; chr13:32973280, A/-, a mononucleotide deletion within the 5'-UTR of exon 27; and chr13:32973924, T/-, a mononucleotide deletion downstream of the gene sequence. To the best of our knowledge, this study was the first to apply next-generation sequencing of the BRCA1 and BRCA2 genes in a Bulgarian population, prompting further investigation for local founder mutations and variants characteristic for this particular region.